Big Data, Machine Learning, and the Social Sciences: Fairness, Accountability, and Transparency - Wallach, Hanna (Medium, 2014)
This essay is a (near) transcript of a talk I recently gave at a NIPS 2014 workshop on “Fairness, Accountability, and Transparency in Machine Learning,” organized by Solon Barocas and Moritz Hardt.